Career aspirations and career success among managers in the Malaysian public sector. - Mohd Rasdi, Roziah; Ismail, Maimunah; Uli, Jegak; Mohd Noah, Sidek (EuroJournals Publishing, Inc., 2009)
The study examined dimensions and levels of career aspirations and their relationships with objective and subjective career success among managers in the Malaysian public sector. The findings revealed heterogeneity of managers’ career aspirations, and therefore, suggest that the respondents were mostly aspired in managerial competence, job security, and sense of service. Further analyses showed that overall career aspirations were not significantly related with objective career success component such as monthly gross incomes and number of promotions. However, objective career success was only positively correlated with managerial competence and technical-functional competence, and negatively correlated with job security. On the other hand, overall career aspirations were significantly related with subjective career success. Besides that, managerial competence, pure challenge, sense of service and entrepreneurial creativity were significantly correlated with subjective career success. Implications for management and suggestions for future research are put forward.